White matter integrity in dementia with Lewy bodies: a voxel-based analysis of diffusion tensor imaging - Nedelska, Zuzana; Schwarz, Christopher G; Boeve, Bradley F; Lowe, Val J; Reid, Robert I; Przybelski, Scott A; Lesnick, Timothy G; Gunter, Jeffrey L; Senjem, Matthew L; Ferman, Tanis J; Smith, Glenn E; Geda, Yonas E; et al. (Neurobiology of aging, 2015)
Many patients with dementia with Lewy bodies (DLB) have overlapping Alzheimer's disease (AD)-related pathology, which may contribute to white matter (WM) diffusivity alterations on diffusion tensor imaging (DTI). Consecutive patients with DLB (n = 30), age- and sex-matched AD patients (n = 30), and cognitively normal controls (n = 60) were recruited. All subjects underwent DTI, 18F 2-fluoro-deoxy-d-glucose, and (11)C Pittsburgh compound B positron emission tomography scans. DLB patients had reduced fractional anisotropy (FA) in the parietooccipital WM but not elsewhere compared with cognitively normal controls, and elevated FA in parahippocampal WM compared with AD patients, which persisted after controlling for β-amyloid load in DLB. The pattern of WM FA alterations on DTI was consistent with the more diffuse posterior parietal and occipital glucose hypometabolism of 2-fluoro-deoxy-d-glucose positron emission tomography in the cortex. DLB is characterized by a loss of parietooccipital WM integrity, independent of concomitant AD-related β-amyloid load. Cortical glucose hypometabolism accompanies WM FA alterations with a concordant pattern of gray and WM involvement in the parietooccipital lobes in DLB.
Keywords: zobrazování difuzních tenzorů; Female; Amyloid beta-Peptides; Lewy Body Disease; ženské pohlaví; White Matter; Anisotropy; lidé; amyloidní beta-protein; týlní lalok; demence s Lewyho tělísky; Male; Aged; glukosa; anizotropie; Diffusion Tensor Imaging; Glucose; Occipital Lobe; lidé středního věku; pozitronová emisní tomografie; senioři; mužské pohlaví; Middle Aged; bílá hmota; Positron-Emission Tomography; Humans